Beyond radicalization: the 3N model and its application to criminal attitudes in high-risk contexts - Jocelyn J. Bélanger (9603968) (2025)
Introduction This research integrates criminological and psychological literature by applying the 3N model of radicalization to predict criminal attitudes. Specifically, we conceptualize “need” as the search for meaning, “networks” as deviant associations, and “narrative” as criminal attitudes. We examine the roles of these factors across diverse cultural contexts and investigate the effectiveness of prosocial models in redirecting the search for meaning away from criminal attitudes. Methods Three studies were conducted to examine the relationships between the search for meaning, deviant associations, and criminal attitudes. Study 1A sampled former inmates in Pakistan (N = 243), while Study 1B (N = 402) and Study 2 (N = 330) focused on at-risk youth in southern Spain. Study 2 further tested a field intervention using positive role models to mitigate the search for meaning and criminal attitudes. Results Findings from Studies 1A and 1B indicate a significant indirect effect of the search for meaning on criminal attitudes, mediated through deviant associations. Additionally, Study 2 demonstrates that exposure to prosocial role models reduces both the search for meaning and criminal attitudes, supporting the effectiveness of intervention strategies. Discussion These findings highlight the utility of the 3N model in understanding criminal attitudes within diverse high-risk contexts. By bridging psychological and criminological perspectives, this research offers a framework for prevention and intervention strategies targeting individuals vulnerable to criminal influences. Other Information Published in: Frontiers in Psychology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fpsyg.2025.1498936